PENGARUH KEPEMIMPINAN TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA TERHADAP KINERJA SEKOLAH NEGERI SE-KOTA PEKANBARU - Wahyuni, Sri Wirda; Zulfadil, Zulfadil; Chairilsyah, Daviq (Jurnal Tepak Manajemen Bisnis, 2018)
This study aims to determine the relationship of leadership to jobsatisfaction job and impact to school performance of SMP Negeri asPekanbaru City. The population in this study included all vice principla isaslo as teachers of the school, amounting to 120 people. The primary datawere collected by questionnaire as the instrument to prove the result of thestudy, to test the hypotheses using Structural Equation Model-Partial leastSquare with Wrap.PLS.5.0. Sampling technique chosen is sensus sampling(120 teachers SMP Negeri of Pekanbaru City). The results showed that: 1)Leadership of School Principla have significant effect on The Teacher of JobSatisfaction, 2) The Teacher of Job Satisfaction influence on Schoolperformance; .3)Leadership of School Principla influence the SchoolPerformance, and 4)Through Teacher of Job Satisfaction have positive andsignificant impact on the School performance, it can be concluded, TheTeacher of Job Satisfaction have an important role in mediating relationsbetween Leadership of School Principla on the School performance.